2023
DOI: 10.1161/hypertensionaha.122.19399
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hypertensive Disorders of Pregnancy and Dementia: a Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Prior meta-analyses report a 2- to 4-fold increased risk of later cardiovascular disease among women with a history of hypertensive disorders of pregnancy (HDP). Given HDP’s vascular underpinnings, it is hypothesized to also be a risk factor for later dementia. We aim to summarize the evidence for the impact of HDP on dementia and consider unique associations between HDP and dementia subtypes. METHODS: Observational studies on the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…A meta-analysis included 5 cohort studies with a total of 183 874 females with and 2 309 705 females without hypertensive disorders in pregnancy to study the risk of subsequent dementia. 93 Any type of hypertensive disorder in pregnancy was associated with a higher risk of subsequent dementia (HR, 1.38 [95% CI, 1.18–1.61]). For dementia subtypes, any hypertensive disorder in pregnancy was associated with higher risk of vascular dementia (HR, 3.14 [95% CI, 2.32–4.24]).…”
Section: High Blood Pressurementioning
confidence: 99%
“…A meta-analysis included 5 cohort studies with a total of 183 874 females with and 2 309 705 females without hypertensive disorders in pregnancy to study the risk of subsequent dementia. 93 Any type of hypertensive disorder in pregnancy was associated with a higher risk of subsequent dementia (HR, 1.38 [95% CI, 1.18–1.61]). For dementia subtypes, any hypertensive disorder in pregnancy was associated with higher risk of vascular dementia (HR, 3.14 [95% CI, 2.32–4.24]).…”
Section: High Blood Pressurementioning
confidence: 99%
“…By contrast, gestational hypertension is associated with a 3.6-fold increase in risk of end stage kidney disease and a 1.5-fold increase in risk of chronic kidney disease 138. Overall, HDP are associated with a 1.4-fold increase in risk of dementia,140 with pre-eclampsia being associated with a 2.6-fold increase in risk of vascular dementia 141. Pre-eclampsia has been associated with a 1.5-fold and 1.8-fold increase in risk of venous thromboembolism and premature mortality, respectively 122.…”
Section: Postnatal Follow-upmentioning
confidence: 98%
“…191 Furthermore, there appears to be a dose effect, with women who experience recurrent preeclampsia facing an even greater risk. 194,213,214 Epidemiological studies have also shown an increased risk of end-stage renal disease, 208,212,215,216 metabolic syndrome, 212 diabetes, 217,218 cognitive dysfunction, [219][220][221] stroke and other neurological complications. 208,221,222 Although sFlt-1 levels fall after delivery, when examined at two years post-partum, we demonstrated that women with a history of preeclampsia had altered angiogenic profiles and insulin resistance compared to women without a history of preeclampsia.…”
Section: Diseasesmentioning
confidence: 99%